Whose Man in Havana? Adventures from the Far Side of Diplomacy - Graham, John W. (Latin American and Caribbean, 2015)
In Whose Man in Havana? the author offers an unconventional, often dark, but more often hilarious view of diplomacy in settings as varied as Haiti, London, the Dominican Republic, the Balkans, Palestine, Paraguay, Guyana, and Kyrgyzstan, including covert monitoring of Soviet military operations in Cuba on behalf of the CIA with the blessing of President Kennedy and Prime Minister Pearson. In a career that spans the Canadian foreign service and international organizations, he was fortunate to be in the right place at interesting, if turbulent, times. Throughout the book he has focussed on the lighter side of people and places, but almost everywhere the dark side intrudes. Graham makes plain that the intersection of the two is frequently black comedy.